Photoionization of optically trapped ultracold atoms with a high-power light-emitting diode - Götz, Simone Andrea; Höltkemeier, Bastian; Amthor, Thomas; Weidemüller, Matthias (Review of scientific instruments, 2013)
Photoionization of laser-cooled atoms using short pulses of a high-power light-emitting diode (LED) is demonstrated. Light pulses as short as 30 ns have been realized with the simple LED driver circuit. We measure the ionization cross section of 85Rb atoms in the first excited state, and show how this technique can be used for calibrating efficiencies of ion detector assemblies.